(untitled) (CIPEEX, 2025)
INTRODUCTION: Glioblastoma (GBM) is the most common and aggressive subtype of primary central nervous system tumor, characterized by high cellular heterogeneity, infiltrative growth, and resistance to standard therapies (surgery, radiotherapy, and chemotherapy). Given the unfavorable prognosis and median survival of less than 15 months, immune-based strategies have been explored as promising alternatives. Among them, therapy with T cells modified by chimeric antigen receptors (CAR-T) has achieved success in hematological malignancies and is currently under investigation for solid tumors, including GBM. OBJECTIVE: This study aims to review recent literature to identify advances, limitations, and future perspectives on the use of CAR-T cells in glioblastoma treatment. METHODOLOGY: A literature review was conducted in digital databases (PubMed, Scopus, and Web of Science), including original articles and reviews published between 2019 and 2025. The following descriptors were used: "glioblastoma," "CAR-T cells," "immunotherapy," and Boolean combinations. Inclusion criteria: preclinical and clinical studies on GBM, publications in English or Portuguese, full-text access. Exclusion criteria: isolated case reports and articles outside the tumor scope. RESULTS: Application of CAR-T cells in preclinical GBM models demonstrated significant tumor burden reduction when targeting IL13Rα2, EGFRvIII, and GD2, particularly through locoregional delivery (intratumoral or intraventricular), which increases concentration and persistence of cells at the tumor site. Phase I clinical trials using CAR-T against IL13Rα2, EGFRvIII, and GD2 confirmed the feasibility and safety of the approach, showing partial and stable responses in some patients, although efficacy was limited by tumor antigenic heterogeneity and short remission duration. Major challenges include escape due to antigen loss or variation, the blood–brain barrier restricting effector cell trafficking, and the immunosuppressive tumor microenvironment, composed of regulatory cells, MDSCs, and anti-inflammatory cytokines, as well as CAR-T exhaustion and low persistence. To overcome these obstacles, emerging strategies include “armored” CAR-T cells with cytokines such as IL-7, CCL19, or IL-12 to enhance expansion and lymphocyte recruitment, synthetic SynNotch systems allowing sequential multi-antigen recognition and fine-tuned activation control, as well as combined approaches integrating CAR-T with oncolytic viruses, checkpoint inhibitors, and localized radiotherapy. Furthermore, advances in humanized and bispecific CAR engineering and personalized tumor phenotyping methods promise to optimize specificity and mitigate tumor escape. CONCLUSION: CAR-T cell therapy represents an innovative perspective for GBM, with promising results in experimental models and initial safety in humans. However, intrinsic tumor and microenvironmental limitations require multifaceted approaches to enhance efficacy and durability. Future investigations should focus on optimizing CAR design, administration routes, and combinatory therapies to overcome current obstacles.